The effect of engaging leadership on work engagement with affects positive as a mediation variable on syariah bank employees in Medan: Pengaruh engaging leadership terhadap keterikatan kerja dengan afek positif sebagai variabel mediasi pada karyawan bank syariah di Kota Medan - Agung prayogi; Vivi Gusrini Ramadani Pohan (Talenta Publisher, 2022)
This research aimed to determine the effect of engaging leadership on work engagement with positive affect as a mediating variable on Islamic Bank employees in Medan City. This study used a quantitative method using questionnaires and involved 100 Islamic Bank employees in Medan City. There are three measuring tools used in this study, namely variables measuring engaging leadership scale (ELS), Utrecht Work Engagement (UWES) and Positive and Negative Affect Schedule (PANAS). The data obtained were processed using IBM Statistical Product and Service Solution (SPSS) and hypothesis testing by WarpPLS 7.0. The results showed that positive affect had a role as a mediator in the relationship between engaging leadership and work engagement for Islamic Bank employees in Medan City (p = 0.000 < 0.05).